Student Perceptions of the Faculty of Social Sciences, State University of Medan Concerning the Dangers of Money Politics Practices in Village Head Elections - Lidya Siboro, Ruth; Mufidah, Anisah; Damanik, Denada; Pratiwi, Dina; Ivanna, Julia (Berpusi Publishing, 2023)
Indonesia is a country that adheres to a democratic system. Democracy is a state in which sovereignty and supreme power are in the hands of the people and then run directly by representatives who have been elected under the general election system. The general election process is from the central government to regional heads, especially the lowest level of government, namely village head elections. Although village head elections are held at the lowest level, the political dynamics that accompany them are not low. One of the things that violates the village head elections that are rife is the practice of money politics. The purpose of this article or writing is to find out about the perceptions of students of the Faculty of Social Sciences, Medan State University regarding the dangers of money politics in village head elections. As for the type of research conducted by the author, namely qualitative research and this type of research is descriptive analysis research then data collection techniques are more on observation and interviews. In this study, the authors conducted direct interviews with students of the Faculty of Social Sciences, Medan State University. Based on the research results, money politics in village head elections is something or a tool that can endanger the electability of village head elections, because this can tarnish and tarnish the meaning of democracy. Another thing that can be found in the results of this study, is that the view of students of the Faculty of Social Sciences, Medan State University towards money politics is something that is absolutely not beneficial in the long run for the community because if you see the use value for the progress of society then this can disrupt the development of the country if people's mindset cannot be critical and intelligent in determining leaders who will strive for the welfare of the community itself in the future. The practice of money politics can be prevented through implementing political education or socializing the dangers of money politics itself among the younger generation.